2009
DOI: 10.1007/s00268-009-0229-6
|View full text |Cite
|
Sign up to set email alerts
|

Global Anesthesia Workforce Crisis: A Preliminary Survey Revealing Shortages Contributing to Undesirable Outcomes and Unsafe Practices

Abstract: BackgroundThe burden of disease, disability, and mortality that could be averted by surgery is growing. However, few low and middle income countries (LMICs) have the infrastructure or capacity to provide surgical services to meet this growing need. Equally, few of these countries have been assessed for key infrastructural capacity including surgical and anesthesia providers, equipment, and supplies. These assessments are critical to revealing magnitude of the evolving surgical and anesthesia workforce crisis, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
140
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 149 publications
(141 citation statements)
references
References 33 publications
1
140
0
Order By: Relevance
“…Other studies have shown a disproportionate increase in death and disability due to these barriers [5][6][7][8]10]. What was surprising in our examination was the inherent complications to creating a global synopsis of anesthetic need; the vast variegations between countries and within countries call into question whether a checklist of essential equipment or a single top down approach to increasing anesthetic capacity is realistic.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…Other studies have shown a disproportionate increase in death and disability due to these barriers [5][6][7][8]10]. What was surprising in our examination was the inherent complications to creating a global synopsis of anesthetic need; the vast variegations between countries and within countries call into question whether a checklist of essential equipment or a single top down approach to increasing anesthetic capacity is realistic.…”
Section: Discussionmentioning
confidence: 57%
“…In sub-Saharan Africa the majority of anaesthetics are provided by non-physician anaesthetic providers working alone, unsupervised, and with limited training [8]. The avoidable mortality rate attributable to anaesthesia in some countries is high (1:150 in Togo, 1:504 in on Central Hospital in Malawi and 1:1923 in another in Zambia) when compared to rates of 0.55 per 100,000 in the United States [9,10]. health organizations, health authorities, civil and professional societies, Non-Governmental Organizations (NGOs) and individuals committed to promoting global emergency, surgery and anesthesia care as part of primary care [11].…”
Section: Introductionmentioning
confidence: 99%
“…12,13 The second major concern is maintenance. 14 The RVM used works on a Microsoft (Redmond, Washington) Windows-based platform and provides an easy avenue for troubleshooting and fixing any malfunction. Additionally, technical support is available by telephone, and the practitioner may communicate via a wireless fidelity application without incurring telephone charges.…”
Section: Discussionmentioning
confidence: 99%
“…12 The 'insufficient, inequitable distributions' of resources in district hospital (DH) needs to be addressed to make 'ESASA' accessible to rural population. 13,14 The observation of 'operative capabilities of 78 DH in seven LMICs 'Bangladesh, Bolivia, Ethiopia, Liberia, Nicaragua, Rwanda, and Uganda' revealed alarming situation of "one surgeons and anesthetists serving up to 100,000 to one million population; inadequate infrastructure, and shortages of essential equipment".…”
Section: 9mentioning
confidence: 99%